Risk factors for potential drug-drug interactions of statins in patients with acute coronary syndrome - Ana V. Pejčić; Slobodan M. Janković; Goran Davidović (Universidade de São Paulo, 2022)
Abstract The aim of our study was to assess risk factors for potential drug-drug interactions (pDDIs) of statins across different phases of treatment of acute coronary syndrome (ACS) patients: from the point of first medical contact to the coronary angiography (first phase), after coronary angiography to the last day of hospitalization (second phase) and at discharge from hospital (third phase). This was a post hoc analysis of the data collected during the retrospective observational cohort study conducted at the Clinic for Cardiology of the Clinical Centre Kragujevac, Serbia. Patients prescribed statins were identified from the original study population: 156, 240 and 236 patients for the first, second and third phases, respectively. At least one statin pDDI was present in 113 (72.4%), 161 (67.1%) and 139 (58.9%) patients in the first, second and third phases, respectively. Heart failure, arrhythmias after ACS, CRP, triglycerides, length of hospitalization, number of prescribed drugs, antiarrhythmic drugs, and clopidogrel seem to increase the risk of statin pDDIs in at least one treatment phase. Physicians should be vigilant to the possibility of statin pDDIs in ACS patients who have factors that may increase their rate.